1991
DOI: 10.1093/schbul/17.2.325
|View full text |Cite
|
Sign up to set email alerts
|

Neuroleptics and the Natural Course of Schizophrenia

Abstract: To determine if neuroleptic treatment changes the natural course of schizophrenia, 22 studies were reviewed in which relatively similar patients were or were not given neuroleptics at specific times during the course of their illness. Nineteen of the studies were from first- or predominantly first-break populations. While there was little consensus among the authors of the studies reviewed, a reanalysis of the data indicates that early intervention with neuroleptics in first-break schizophrenic patients increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
353
4
12

Year Published

1992
1992
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 673 publications
(383 citation statements)
references
References 65 publications
12
353
4
12
Order By: Relevance
“…Stabilized chronic schizophrenic patients whose antipsychotic medications were discontinued had an 80% relapse rate compared with 23% of patients maintained on antipsychotic medications (Johnson et al, 1983). Significantly, even after a minimum of 6 months following the reinstitution of antipsychotic medications, the patients who had relapsed had not recovered the social adjustment they would have achieved had they not been taken off antipsychotic medications (Wyatt, 1991). Taken together, the studies by Curson and colleagues and Johnson and colleagues suggest that, while a brief placebo period and a relapse that occurs because of it may not have a large long-term effect on a group of already chronically ill schizophrenic patients, the apparently slow recovery period is an issue that must be considered.…”
Section: Evidence From Discontinuation Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Stabilized chronic schizophrenic patients whose antipsychotic medications were discontinued had an 80% relapse rate compared with 23% of patients maintained on antipsychotic medications (Johnson et al, 1983). Significantly, even after a minimum of 6 months following the reinstitution of antipsychotic medications, the patients who had relapsed had not recovered the social adjustment they would have achieved had they not been taken off antipsychotic medications (Wyatt, 1991). Taken together, the studies by Curson and colleagues and Johnson and colleagues suggest that, while a brief placebo period and a relapse that occurs because of it may not have a large long-term effect on a group of already chronically ill schizophrenic patients, the apparently slow recovery period is an issue that must be considered.…”
Section: Evidence From Discontinuation Studiesmentioning
confidence: 99%
“…Nine mirror-image studies have been identified (Wyatt, 1995a(Wyatt, , 1991, and all but two indicate that there was improvement in the long-term course of schizophrenia after the introduction of antipsychotic medications (Table 1). One study by Astrup and Noreik (1966), shown in Table 2, found that first-episode patients admitted to Oslo's Gaustad Hospital were more likely to do worse if they were admitted in the pre-antipsychotic medication era (1938 to 1950) than if they were admitted during the antipsychotic medication era (1951 to 1957).…”
Section: Mirror-image Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Individuals who receive antipsychotic prophylaxis (maintenance therapy) have been found to have a better outcome than those who have antipsychotics only when symptoms are present. 61,62 Non-compliance is also often related to efficacy limitations as well as ADRs of antipsychotics, 63 increasing the risk and severity of relapse (with each further episode a decline in baseline functioning can be expected 64 ), increasing the length of hospital stay and quadrupling the risk of suicide attempts. 65 It has been found that 10 days after discharge from hospital up to 25% of individuals with schizophrenia are partially or non-compliant, rising to 50% after 1 year and 75% after 2 years.…”
Section: Schizophreniamentioning
confidence: 99%
“…8 Poor maintenance therapy with successive relapses can reduce the patients' functioning and increases chances of developing refractoriness to future treatments. 9 Therefore it is well established that antipsychotics represent the mainstay of treatment for schizophrenia although consensus panel recommendations regarding choice of an antipsychotic agent for schizophrenia sometimes differ. The conventional antipsychotics with high-affinity for dopamine D2 receptors are the most effective against psychotic symptoms but have high rates of neurological side effects, such as extra-pyramidal signs (EPS) and tardive dyskinesia.…”
Section: Introductionmentioning
confidence: 99%